Socio-economic changes after the launch of the lignite mine and the “Bełchatów” power plant and their social perception. Case of Kleszczów commune (Poland) - Kulawiak, Anita; Suliborski, Andrzej (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2022)
The article focuses on two main problems. On the one hand, it presents the changes that have taken place in the Kleszczów commune (Poland) in the demographic and economic sphere under the influence of the launch of the “Bełchatów” mining and energy plant in its area. On the other hand, it presents the contemporary awareness and perception of this place by the people living in the commune, with particular emphasis on social relations and the opinion of residents about its immediate future. The empirical basis of the study were materials and information collected during field and inhouse surveys. The source of data were both official statistical data of the Central Statistical Office for the years 1970-2020, as well as questionnaire interviews with residents of the commune and selected Internet forums of residents. The survey was conducted on a group of 130 inhabitants of the commune, which accounted for 3% of their total number. The analysis of the collected material revealed that the construction of the mining and metallurgical plant caused many irreversible changes in the geographical space of the Kleszczów commune, which concerned the natural and socio-economic sphere. There were also great population changes resulting from migration movements, which created a new, heterogeneous local community of the commune. Parallel to the stages of industrialisation and urbanisation of this area, the attitudes of residents towards their place of residence have also evolved.